1999
DOI: 10.1093/glycob/9.12.1337
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation alterations of cells in late phase apoptosis from colon carcinomas

Abstract: Comparisons of carbohydrate profiles between control and apoptotic colon carcinoma cells were performed by flow cytometry using a set of lectins and anti-carbohydrate antibodies. The six cell lines analyzed presented distinct carbohydrate profiles before induction of apoptosis. PHA-L and MAA binding decreased after induction of apoptosis by UV-treatment. In contrast an increase of PNA binding was observed after induction of apoptosis, except on SW-48 cells for which a decrease occurred. A decrease of SNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Changes in the glycomic profile of apoptotic cells have previously been studied by various groups, who have analyzed cells of different origin (Azuma et al, 2002;Hart et al, 2000;Rapoport and Pendu, 1999). In these previous studies, both an increase and a decrease of membrane-bound Sias have been reported, depending on the cell type under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the glycomic profile of apoptotic cells have previously been studied by various groups, who have analyzed cells of different origin (Azuma et al, 2002;Hart et al, 2000;Rapoport and Pendu, 1999). In these previous studies, both an increase and a decrease of membrane-bound Sias have been reported, depending on the cell type under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IFNg alone up-regulates FUT4 mRNA in HT-29 cells, and expression of all blood group-related antigens, including Lewis X and Y antigens, are suppressed in late apoptosis. 29) IFNg and some chemotherapeutic drugs also up-regulate Lewis Y antigens on HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fucosecontaining carbohydrates play important roles in diverse cellular and physiologic processes, including inflammatory responses (16 -18) and antigenic determination (19). Furthermore, altered expression of ␣-L-fucosidases and corresponding changes in fucosylation levels are seen in many carcinomas (20,21). Accordingly, the presence of human ␣-L-fucosidase in the serum can be used as an early detection marker for several carcinomas (22)(23)(24).…”
mentioning
confidence: 99%